Typological characteristics of the Kazakh family folklore - MUKHAN, A; YERDEMBEKOV, B; MATYZHANOV, K; ISBEK, B (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In the article, some aspects of wedding traditions in Kazakh folklore have been studied with the traditions and customs of the world’s nations. The object of the study is the typological nature of kyzuzatu tradition and the formulation of the old-fashioned concept of the betashar genre in the tradition of meeting the bride. The main point of the article is the scientific conclusions made by analyzing the values of family folklore and their educational significance, which have been forming for centuries, comparing them with the traditions of the world’s nations.RESUMEN En el artículo se han estudiado algunos aspectos de las tradiciones nupciales en el folklore kazajo con las tradiciones y costumbres de las naciones del mundo. El objeto del estudio es la naturaleza tipológica de la tradición kyzuzatu y la formulación del concepto anticuado del género betashar en la tradición de conocer a la novia. El punto principal del artículo es que las conclusiones científicas se obtienen al analizar los valores del folclore familiar y su importancia educativa, que se han estado formando durante siglos, comparándolos con las tradiciones de las naciones del mundo.